2022
DOI: 10.1021/acs.jpcc.2c03012
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Characterization of an Intermediate of CO2 Electroreduction on a Au Electrode in Room-Temperature Ionic Liquids

Abstract: Room-temperature ionic liquids (RTILs) are fascinating electrolytes for CO 2 electroreduction owing to their low overpotentials. Although it is well accepted that the key to understanding the low overpotential is the stabilization of the intermediate, its mechanism is still under discussion. To elucidate the intermediate stabilization mechanism, RTIL/electrode interfaces under CO 2 reduction were observed using surface-enhanced infrared absorption spectroscopy (SEIRAS). This in situ interfaceselective spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 47 publications
(76 reference statements)
2
10
0
Order By: Relevance
“…In ATR–SEIRAS using PAQ under CO 2 , the IR peak assignable to the asymmetric stretching vibration of CO 2 , ν as (CO 2 ), was observed at 2200 cm –1 , which was estimated to have been caused by the CO 2 molecule correlated with AQ by isotope experiments. Previous studies have indicated that the lower wavenumber in comparison to that of free CO 2 (2396 cm –1 ) is due to adsorption and that the shift in wavenumber of CO 2 by physical adsorption is less than the shift caused by chemisorption. ,, Especially, Motobayashi et al have studied the shift of the peak attributable to CO 2 as a result of its strong adsorption on the Au film at a higher negative potential of −2.6 V versus Fc/Fc + , which is similar to the present study of ATR–SEIRAS measurements in aprotic conditions under CO 2 . On the basis of the results of ATR–SEIRAS measurements and DFT calculations, the peak at 2200 cm –1 is presumed to be CO 2 physisorbed on the AQ unit of PAQ, although there is no clear evidence.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In ATR–SEIRAS using PAQ under CO 2 , the IR peak assignable to the asymmetric stretching vibration of CO 2 , ν as (CO 2 ), was observed at 2200 cm –1 , which was estimated to have been caused by the CO 2 molecule correlated with AQ by isotope experiments. Previous studies have indicated that the lower wavenumber in comparison to that of free CO 2 (2396 cm –1 ) is due to adsorption and that the shift in wavenumber of CO 2 by physical adsorption is less than the shift caused by chemisorption. ,, Especially, Motobayashi et al have studied the shift of the peak attributable to CO 2 as a result of its strong adsorption on the Au film at a higher negative potential of −2.6 V versus Fc/Fc + , which is similar to the present study of ATR–SEIRAS measurements in aprotic conditions under CO 2 . On the basis of the results of ATR–SEIRAS measurements and DFT calculations, the peak at 2200 cm –1 is presumed to be CO 2 physisorbed on the AQ unit of PAQ, although there is no clear evidence.…”
Section: Resultssupporting
confidence: 89%
“…52,61,62 Especially, Motobayashi et al have studied the shift of the peak attributable to CO 2 as a result of its strong adsorption on the Au film at a higher negative potential of −2.6 V versus Fc/Fc + , which is similar to the present study of ATR−SEIRAS measurements in aprotic conditions under CO 2 . 52 On the basis of the results of ATR− SEIRAS measurements and DFT calculations, the peak at 2200 cm −1 is presumed to be CO 2 physisorbed on the AQ unit of PAQ, although there is no clear evidence. In addition, the peak at 2200 cm −1 is very weak, which correlates well with small ΔG of −7.3 kJ/mol for AQ−(CO 2 − ) 2 .…”
Section: ■ Experimental Proceduressupporting
confidence: 85%
See 2 more Smart Citations
“…Another advantage of RTILs is their ability to stabilize EC CO 2 RR reaction intermediates, such as the CO 2 •- anion radical that is the rate-determining step (RDS) of the reaction at high current densities 27 . For instance, Motobayashi et al 28 observed RTIL cations stabilizing the CO 2 •- radical intermediate by using surface-enhanced infrared absorption spectroscopy (SEIRAS). Ratschmeier et al 29 also demonstrated the CO formation via an electrostatically stabilized CO 2 •- radical by the RTILs cation by using in operando IR absorption spectroscopy and in situ sum-frequency generation spectroscopy.…”
Section: Introductionmentioning
confidence: 99%